2014
DOI: 10.3390/ijms151018175
|View full text |Cite
|
Sign up to set email alerts
|

Argon: Systematic Review on Neuro- and Organoprotective Properties of an “Inert” Gas

Abstract: Argon belongs to the group of noble gases, which are regarded as chemically inert. Astonishingly some of these gases exert biological properties and during the last decades more and more reports demonstrated neuroprotective and organoprotective effects. Recent studies predominately use in vivo or in vitro models for ischemic pathologies to investigate the effect of argon treatment. Promising data has been published concerning pathologies like cerebral ischemia, traumatic brain injury and hypoxic ischemic encep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 39 publications
2
42
0
Order By: Relevance
“…Argon, another noble gas, possesses similar protective properties 20 . However, the neuro-protective potential of argon combined with hypothermia has not been explored to date.…”
Section: Discussionmentioning
confidence: 99%
“…Argon, another noble gas, possesses similar protective properties 20 . However, the neuro-protective potential of argon combined with hypothermia has not been explored to date.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we investigated the mRNA levels of representative genes which, especially in the first few hours after hepatectomy (“priming phase”), are of particular importance [2,21]. Additionally, a connection to the previously proven effects of argon on these genes should exist [8,13]. …”
Section: Resultsmentioning
confidence: 99%
“…Since then, different studies have demonstrated argon's protective effect on various cells and organs. This virtue has been proven for the sensory cells of the inner ear [4] and the retina [5] and for the neuronal cells of the cerebrum [6,7,8,9], as well as for individual organ functions including kidney and heart protection [10,11,12]. However, the underlying protective mechanisms are only partly understood.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations